Estudio de prefactibilidad para la instalación de una planta productora de dentífrico en forma de pastillas - Mendoza Rojas, Claudia Melissa (2020)
The purpose of this study is to determine the commercial, technical, economic-financial and social viability of the installation of a toothpaste-producing plant in the form of pills in Metropolitan Lima. Currently, plastic pollution increasingly affects the planet, and toothpastes in plastic tubes are no stranger to this problem. Given this, a toothpaste is proposed in the form of pills with high quality standards, in reusable and easily recyclable glass jars. In the market study, it was obtained that the demand of the project would be 16 721 boxes of 24 bottles in the fourth year of operation. The final consumers are people who live in Metropolitan Lima, who use toothpaste in tooth brushing, between 18 and 55 years of age and and that belong to socioeconomic levels A or B. Likewise, it was decided to have three product lines: standard, whitening and without fluorine. About the location of the plant, it was determined that the optimal district would be Lurín, mainly due to the number of industrial areas and the low cost of rent per square meter. Subsequently, in the chapter about plant size, it was obtained that this would be limited by market size, with a value of 16 721 boxes. Also, with respect to the production process, direct compression technology will be used to produce the solid toothpaste, in a process known as Tableting. In the chapter about budgets and evaluation of the project, it was estimated that the total investment of the project would amount to S/ 1 050 005, which include tangible investment, intangible investment and working capital. The economic evaluation is then carried out, where a Net Present Economic Value of S/ 1 109 872 and an Internal Economic Return Rate of 53,1% are obtained. Finally, in the financial evaluation, a Net Financial Present Value of S/ 51 179 357, and an Internal Financial Return Rate of 67,8% are obtained. These indicators demonstrate that the project is profitable.